Measuring vertical atmospheric profiles using low-cost balloon probes equipped with open technologies - Chuquihuanca-Carhuapoma, Rolyn; Honorio-Choquehuanca, Patrick; Juárez Ortiz, Vladimir Adolfo (International Journal of Computational Innovations, Intelligent Systems and AI, 2025)
This experimental work presents the design, assembly, and launch of an atmospheric exploration platform with a weather balloon, payload, and parachute, built from low-cost materials and incorporating digital sensors and wireless transmission for real-time data recording. The system enabled real-time measurement of key variables such as temperature, atmospheric pressure, relative humidity, ultraviolet radiation, and ozone concentration, generating vertical profiles over the coast of Piura, Peru. The methodology included the selection and acquisition of sensors, microcontroller programming, calibration under controlled conditions, functional testing, and analysis of the data recorded during the flight. The results obtained provide valuable information on the thermal structure and dynamics of the troposphere and stratosphere, confirming the technical feasibility of cost-effective platforms for mid-altitude atmospheric studies. This work sets a precedent for the development of environmental monitoring systems in regions with limited infrastructure and opens future opportunities for the integration of more advanced sensors and real-time data transmission systems, with both scientific and educational applications.